Fulfillment of Women's Rights After Divorce in Religious Courts as Protection for Vulnerable Groups: An Islamic Law and Gender Justice Perspective - Sri Armaini; Ismail Koto (Pancasila and Civics Education Journal (PCEJ), 2026)
Abstract: Marriage creates reciprocal rights and obligations between husband and wife, including the husband's obligation to provide maintenance in the form of living expenses, clothing (kiswah), and housing (maskan). However, marital disputes may lead to divorce as a last resort when reconciliation can no longer be achieved. In Indonesia, divorce is regulated under Law Number 1 of 1974 concerning Marriage, which defines marriage as a physical and spiritual bond aimed at forming a happy and enduring family based on belief in God Almighty. Following the issuance of Supreme Court Regulation (PERMA) concerning the implementation of women's rights after divorce, judges may order the payment of iddah maintenance, mut’ah, and outstanding maintenance (nafkah madliyah) before the pronouncement of the divorce oath. This provision is intended to strengthen legal protection for women after divorce. Nevertheless, the implementation of post-divorce rights remains inconsistent. In practice, some court decisions have not fully reflected the principles of justice and legal protection for women, resulting in unequal fulfillment of their rights. Therefore, a more comprehensive approach is needed to ensure that post-divorce legal protection effectively promotes justice, legal certainty, and welfare, particularly for women as a vulnerable party in divorce proceedings.Keywords: Rights, Women, Divorce, Islam, Justice.Abstrak: Perkawinan menciptakan hak dan kewajiban timbal balik antara suami dan istri, termasuk kewajiban suami untuk memberikan nafkah berupa biaya hidup, pakaian (kiswah), dan tempat tinggal (maskan). Namun, perselisihan perkawinan dapat berujung pada perceraian sebagai upaya terakhir ketika rekonsiliasi tidak lagi dapat dicapai. Di Indonesia, perceraian diatur dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, yang mendefinisikan perkawinan sebagai ikatan fisik dan spiritual yang bertujuan membentuk keluarga bahagia dan langgeng berdasarkan kepercayaan kepada Tuhan Yang Maha Esa. Menyusul diterbitkannya Peraturan Mahkamah Agung (PERMA) tentang pelaksanaan hak-hak perempuan setelah perceraian, hakim dapat memerintahkan pembayaran nafkah iddah, mut’ah, dan nafkah tertunggak (nafkah madliyah) sebelum pengucapan sumpah cerai. Ketentuan ini dimaksudkan untuk memperkuat perlindungan hukum bagi perempuan setelah perceraian. Meskipun demikian, pelaksanaan hak-hak pasca-perceraian masih belum konsisten. Dalam praktiknya, beberapa keputusan pengadilan belum sepenuhnya mencerminkan prinsip-prinsip keadilan dan perlindungan hukum bagi perempuan, sehingga mengakibatkan pemenuhan hak-hak mereka yang tidak setara. Oleh karena itu, diperlukan pendekatan yang lebih komprehensif untuk memastikan bahwa perlindungan hukum pasca perceraian secara efektif mendorong keadilan, kepastian hukum, dan kesejahteraan, khususnya bagi perempuan sebagai pihak yang rentan dalam proses perceraian.Kata Kunci: Hak, Perempuan, Perceraian, Islam, Keadilan